Sulfur treated 1D anodic TiO2 nanotube layers for significant photo- and electroactivity enhancement - Krbal, Milos; Ng, Siow Woon; Motola, Martin; Hromadko, Ludek; Dvorak, Filip; Prokop, Vit; Sopha, Hanna; Macak, Jan M. (Applied Materials Today, 2019)
In this work, we show that sulfur treated 1D anodic TiO2 nanotube layers lead to improved photo-electrochemical and catalytic properties compared to the blank nanotube layers. This treatment was performed in the evacuated quartz ampoules in the temperature range from 250 to 450 °C. Inspection of the sulfurized nanotube layers via scanning electron microscopy (SEM) and X-ray diffraction (XRD) has disclosed a gradual crystal growth within nanotube walls, represented by TiS2 or TiS3 phases. Optimally sulfurized TiO2 nanotube layers exhibit 3 times enhanced photocurrent in the UV spectral region, compared to the blank counterpart, with a shift of the light absorption up to the wavelength of 550 nm. In addition, the photocatalytic decomposition of a methylene blue aqueous solution using a wavelength of 365 nm is gradually improved with increasing sulfurization temperature. The highest photocatalytic decomposition rate is 2.3 times larger compared to the blank TiO2 nanotube layer. The application of sulfurized TiO2 nanotube layers for the electrocatalytic hydrogen evolution is also discussed.
CRIS-Team Scopus Importer:2022-11-02
Keywords: Photocatalysis; Photocurrent; Photoelectrochemistry; Sulfurization; TiO